On the spine of two-particle Fleming-Viot process driven by Brownian motion - Burdzy, Krzysztof; Tadić, Tvrtko (Electronic Communications in Probability, 2024)
The spine of two-particles Fleming-Viot process driven by Brownian motion is not a Bessel-3 process.